Manifestações patológicas presentes em residências habitacionais do município de Nova Jaguaribara-Ce - Freire, Valéria Parente (Universidade Federal Rural do Semi-Árido, 2019)
In the most part of the cases, the emergence of the pathological manifestations can cause complications and excessive concern to the involved with the impaired buildings, causing problems and prejudice in the total loss or partial of the performance of the materials or structures that are suffering these manifestations, limiting thus, the service life and the performance of the same. This study had by purpose accomplished a study of the pathological manifestations found in the residential residences of the county of Nova Jaguaribara – CE. The present study was developed in the city of Nova Jaguaribara, localized in the region of the valley of the low Jaguaribe, to 227 km of Fortaleza, capital of Ceará. The study was accomplished in the urban area of the city, it were visited 30 residences of the city center for identification and record photographic of the pathological manifestations more presents in the civil construction. In the occasion was applied a form (in appendix) to responsible of the residence about the level of knowledge of the pathologies found. After the application of the questionnaire was accomplished a study to from of the identification of the pathological manifestations presents in the residence studied. The residences of the city of Nova Jaguaribara independent of the time of construction presented pathological manifestations similar, that is, the constructions with more of 10 years of service life and the with less of 5 years, with built areas with more of 100m² or minors of 80m². The major index found of the pathological manifestations studied is the of the efflorescence followed of mold, it was verified that the rain is the principal cause of these manifestations in the their large majority. Parallel, it is observed also the presence of the humidity provoked mainly by the rains, since, when is related with the pathological manifestations can realize the damages occasioned by same, since the its smaller index of gravity until the damages more grave, can come afloat large complications, rich of life and elevated costs that would can have been avoids. The majority of the residences with 17 years of time of construction presented the pathological manifestation related with the efflorescence and mold and the with less time of construction with others pathological manifestations, highlighting the displacement of floor and ceramic material. It were observed that the main agents responsible by emergence of these pathological manifestations, are natural factors as rains and humidity. Thus, it is recognized the importance of this study, in order to observe, identify and take knowledge in relation to how to avoid the pathological manifestations or how to repair.
Monografia
Keywords: Eflorescência; Construção Civil; Nova Jaguaribara-CE; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA